2018
DOI: 10.1021/acsami.8b02448
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Porous Microcarriers Based on Strontium-Substituted HA-g-Poly(γ-benzyl-l-glutamate) for Bone Tissue Engineering

Abstract: Porous microcarriers have aroused increasing attention recently, which can create a protected environment for sufficient cell seeding density, facilitate oxygen and nutrient transfer, and well support the cell attachment and growth. In this study, porous microcarriers fabricated from the strontium-substituted hydroxyapatite- graft-poly(γ-benzyl-l-glutamate) (Sr10-HA- g-PBLG) hybrid nanocomposite were developed. The surface grating of PBLG, the micromorphology and element distribution, mechanical strength, in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 60 publications
(96 reference statements)
1
34
0
1
Order By: Relevance
“…The main mechanism is thought to lie in Sr ion possessing the ability not only to enhance the osteogenesis differentiation of MSCs via phosphating the Ras/MAPK signaling pathway but also to suppress the osteoclastogenic differentiation by inhibiting RANKL expression in MSCs [54]. Investigators had also indicated that Sr-contained HA cement and scaffolds could promote early angiogenesis after implantation into the critical size of bone defect and significantly enhance new bone regeneration [55,56].…”
Section: Resultsmentioning
confidence: 99%
“…The main mechanism is thought to lie in Sr ion possessing the ability not only to enhance the osteogenesis differentiation of MSCs via phosphating the Ras/MAPK signaling pathway but also to suppress the osteoclastogenic differentiation by inhibiting RANKL expression in MSCs [54]. Investigators had also indicated that Sr-contained HA cement and scaffolds could promote early angiogenesis after implantation into the critical size of bone defect and significantly enhance new bone regeneration [55,56].…”
Section: Resultsmentioning
confidence: 99%
“…Porous microcarriers were fabricated from the nanocomposites of strontium-substituted hydroxyapatite-graft-poly (γ-benzyl L-glutamate) [103]. It was confirmed by confocal microscopy that the seeded rabbit adipose-derived stem cells (ADSCs) adhered and infiltrated within the internal pores of the microspheres.…”
Section: Understanding Of Real 3d Cell Culture and Challengesmentioning
confidence: 94%
“…Recently, the field of bone tissue engineering (BTE) has been developing rapidly, and various promising biomaterials have emerged and have been widely applied for bone repair and regeneration (11,12). The use of osteogenic cells combined with various growth factors and biocompatible scaffolds can greatly promote bone repair.…”
Section: Introductionmentioning
confidence: 99%